ANALISIS MORFOMETRIK, MERISTIK SIPUT Litorina scabra PADA HUTAN MANGROVE PERAIRAN PANTAI DESA SULI KABUPATEN MALUKU TENGAH - Arini, Ine; Aska, Aska (BIOPENDIX: Jurnal Biologi, Pendidikan dan Terapan, 2021)
Backgroud: Littorina is a type of mollusk, the Gastropod class that lives in tidal areas of sea water and is distributedfrom tropical to subtropical waters. Littorina is a source of animal protein for coastal communities, especially in thecoastal area of Suli Village. It has a shell that houses or armor. Its shell has quite varied morphometric and meristiccharacteristics.Metode: Morphometric measurements include shell length, shell width, thread length and thread width using ImageRaster Viewer 3.0 and Micconos Optilab Viewer 3.0 software. Meristic calculations are done manually by counting thenumber or level of threads on the Littorina.Hasil: The results showed that the mean shell length was 36.04, shell width 21.67 mm, thread length 10.41 mm, andthread width 6.55 mm. Meristic calculation results are the value of 5 to 7 the number or level of threads in the Littorinascabra. Environmental parameters in Suli Village Beach are also in good condition for marine life including littorina.Coclusion: The morphomteric characters of the studied littorina varied. Littorina has a shell length range (SL) of20.47 - 66.13 mm and a shell width (SW) of 12.61 - 34.01 mm. Thread length (AL) ranges from 8.50 - 12.28 mm andthread width (AW) 4.56 - 8.47 mm. The number of spires is 5-7 for maximum size, 6-7 for medium size and 6 forminimum size. Meanwhile, environmental parameters are still in the normal range for marine biota, especially Littorinascabra, namely a temperature of 290 C, a pH of 8.0, a salinity of 380/00 and the amount of dissolved oxygen is 4 mg/ L.